Centromedian thalamic neuromodulation for the treatment of idiopathic generalized epilepsy - Zillgitt, Andrew J.; Haykal, M. Ayman; Chehab, Ahmad; Staudt, Michael D. (Frontiers in Human Neuroscience, 2022)
Idiopathic generalized epilepsy (IGE) is a common type of epilepsy and despite an increase in the number of available anti-seizure medications, approximately 20-30% of people with IGE continue to experience seizures despite adequate medication trials. Unlike focal epilepsy, resective surgery is not a viable treatment option for IGE; however, neuromodulation may be an effective surgical treatment for people with IGE. Thalamic stimulation through deep brain stimulation (DBS) and responsive neurostimulation (RNS) have been explored for the treatment of generalized and focal epilepsies. Although the data regarding DBS and RNS in IGE is limited to case reports and case series, the results of the published studies have been promising. The current manuscript will review the published literature of DBS and RNS within the centromedian nucleus of the thalamus for the treatment of IGE, as well as highlight an illustrative case.